2021
DOI: 10.18203/2394-6040.ijcmph20213517
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of female genital mutilation among health care workers in Somali region of Ethiopia

Abstract: Background: Female genital mutilation (FGM) is a global challenge with estimated over two hundred million girls and women worldwide having undergone the procedure and another three million girls are at risk of being cut yearly. The prevalence of FGM among women and girls aged 15-49 years in Somali region of Ethiopia is 99% compared to the national average of 65%. The study assessed the knowledge, attitude, and practice of health care workers on FGM practices in the region.Methods: The study was a cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The study reported that Southern Nations, Nationalities, and People's Region (SNNPR) region was the only region in which there was some involvement of medical personnel with 1 in 10 women who underwent FGM done by doctors, nurses, midwives, or other health professionals. However recent studies done in Afar and Somali regions indicated that some health workers even though they believe it's against human rights, supported and practiced medicalization of 'Sunnah cut' type 1 of circumcision because of their religious belief, and also because of their perception that it makes FGM safer compared to the traditional method by reducing the risk of infibulation and medical complications [25,26]. The studies reported that 20 per cent (Afar) and 55.5 per cent (Somali) healthcare providers from hospitals; 30 per cent (Afar), and 36 percent (Somali) of health care providers from health centres, admitted to having practiced FGM [25,26].…”
Section: Medicalization Of Fgmmentioning
confidence: 99%
See 3 more Smart Citations
“…The study reported that Southern Nations, Nationalities, and People's Region (SNNPR) region was the only region in which there was some involvement of medical personnel with 1 in 10 women who underwent FGM done by doctors, nurses, midwives, or other health professionals. However recent studies done in Afar and Somali regions indicated that some health workers even though they believe it's against human rights, supported and practiced medicalization of 'Sunnah cut' type 1 of circumcision because of their religious belief, and also because of their perception that it makes FGM safer compared to the traditional method by reducing the risk of infibulation and medical complications [25,26]. The studies reported that 20 per cent (Afar) and 55.5 per cent (Somali) healthcare providers from hospitals; 30 per cent (Afar), and 36 percent (Somali) of health care providers from health centres, admitted to having practiced FGM [25,26].…”
Section: Medicalization Of Fgmmentioning
confidence: 99%
“…However recent studies done in Afar and Somali regions indicated that some health workers even though they believe it's against human rights, supported and practiced medicalization of 'Sunnah cut' type 1 of circumcision because of their religious belief, and also because of their perception that it makes FGM safer compared to the traditional method by reducing the risk of infibulation and medical complications [25,26]. The studies reported that 20 per cent (Afar) and 55.5 per cent (Somali) healthcare providers from hospitals; 30 per cent (Afar), and 36 percent (Somali) of health care providers from health centres, admitted to having practiced FGM [25,26]. These findings indicate that medicalizing the practice of the 'sunah' type is becoming increasingly common and a way of encouraging the practice of FGM to continue in most part of Ethiopia like Afar and Somali regions of Ethiopia.…”
Section: Medicalization Of Fgmmentioning
confidence: 99%
See 2 more Smart Citations
“…Many countries have ratified and deposited the Maputo Protocol, which promotes women’s rights, including an end to FGM/C [ 18 ]. A majority of respondents in the cited studies agreed with the view that the FGM/C procedure violates human rights [ 19 ]. This applies both to the self-determination of one’s own body and to the woman’s right to experience pleasure, which she is deprived of by removing the clitoris.…”
Section: Introductionmentioning
confidence: 99%